The Effect of Logistic Service Quality on Customer Satisfaction and Loyalty in E-Commerce in Indonesia: A Study on Generation Z in Indonesia - Masniarara Aziza Balfas Amril; Wahyuningsih Santosa; Triwulandari Satitidjati Dewayana; Atiqa Firani Balfas Amril (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the influence of logistics service quality on customer satisfaction and loyalty among Generation Z in the Indonesian e-commerce context. Logistics Service Quality (LSQ) is measured through six dimensions: personnel contact quality, timeliness, order condition, order discrepancy handling, operational information sharing, and empathy quality. A quantitative approach using Partial Least Squares – Structural Equation Modeling (PLS-SEM) was applied, with data collected from 155 Generation Z e-commerce users. The findings reveal that all LSQ dimensions significantly affect customer satisfaction, and satisfaction strongly influences customer loyalty (R² = 0.820). These results highlight the critical role of logistics service quality as a key determinant of satisfaction and loyalty among young digital consumers.